Satisfaction of Outpatients and Inpatients with Psychiatric Services at Allama Iqbal Memorial Hospital, Sialkot (Medical Forum Monthly, 2024)
Objective: The objective of the current study was to assess satisfaction of outpatients and inpatients with psychiatric services and to compare the satisfaction level of both groups of patients to understand areas to be improved in delivery of psychiatric care.Study Design: Observational / descriptive / cross sectional study.Place & duration of study: This study was conducted at the Department of Psychiatry & Behavioural Sciences, Government Allama Iqbal Memorial Teaching Hospital affiliated to Khawaja Muhammad Safdar Medical College Sialkot, Pakistan from August 2015 to July 2016.Material and methods: Sample size was 600 patients; including 300 outpatients and 300 inpatients. Patients aged 18 years or above, from both genders, who gave written informed consent, were consecutively included in the study. Excluded from the study were the patients with mental retardation, delirium, impairment of cognition, severe medical illness and severe psychotic symptoms. Demographic information of the patients was taken on a pre-designed proforma. Urdu version of the Client Satisfaction Questionnaire 8 (CSQ-8) was administered to assess patient satisfaction. The results were analyzed using SPSS version 21.Results: Among the outpatients there were 67.7% patients mostly satisfied, 22% mildly satisfied and 10.3% dissatisfied. While in the inpatients there were 68% mostly satisfied, 22.3% mildly satisfied and 9.7% dissatisfied with the psychiatric services. Only age was significantly associated with satisfaction.Conclusion: Most of the outpatients and inpatients were satisfied with the psychiatric services. The outpatients and inpatients were almost equally satisfied. Older patients were more satisfied than the younger patients. Other demographic variables like gender, marital status, education and economic status did not influence the satisfaction.